2014
DOI: 10.4172/2329-6607.1000115
|View full text |Cite
|
Sign up to set email alerts
|

Supraphysiological Testosterone Levels Shorten the QT Interval but do Not Alter Total Anatomic Myocardial Infarct Size in Rabbits with Acute Myocardial Infarction

Abstract: Introduction: A growing number of men are using exogenous testosterone (T) to treat hypogonadism and to enhance athletic performance. However, some studies suggested that T increased adverse cardiovascular events. Although T has been shown to increase apoptosis, its effect on total acute myocardial infarction (MI) size is largely unknown. We hypothesized that T might increase MI size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…As shown in Tables and , both positive and negative effects of testosterone have been described. In a recent study from our group, exogenous testosterone had no effect on experimental myocardial infarct size and shortened the QTc interval (which results in a less arrhythmogenic milieu) on the electrocardiogram (ECG) [3].…”
Section: Introductionmentioning
confidence: 85%
“…As shown in Tables and , both positive and negative effects of testosterone have been described. In a recent study from our group, exogenous testosterone had no effect on experimental myocardial infarct size and shortened the QTc interval (which results in a less arrhythmogenic milieu) on the electrocardiogram (ECG) [3].…”
Section: Introductionmentioning
confidence: 85%
“…83 However, the supraphysiological dose of testosterone replacement (500 and 50 mg/kg) in the myocardial infarction and I/R models exerted neither adverse effect nor infarct size reduction benefits. 84,85 It is of interest to note from these findings that physiological levels or low doses of testosterone may provide a cardioprotective effect against I/R injury. Most of the positive effects of testosterone on the infarct size in I/R models also occurred in the combination of testosterone supplement and conditional treatments, including I/R preconditioning and adrenergic receptor stimulation.…”
Section: Testosterone and The Pathological Heartmentioning
confidence: 99%
“…82 Interestingly, supraphysiological doses of both testosterone and its metabolite (5a-dihydrotestosterone [DHT]) also exhibited a beneficial effect on cardiac function during I/R injury by attenuating intracellular Ca 2þ overload during the reperfusion period, 24,86 whereas the supraphysiological dose of testosterone replacement (50 mg/kg) in another I/R model exerted neither adverse nor beneficial effect on cardiac function. 85 This suggests that testosterone plays a cardioprotective role by reducing intracellular acidification resulting in the maintenance of physiological cytosolic Ca 2þ levels during ischemic stress. 86 In addition, echocardiographic study also demonstrated that testosterone replacement therapy (2 mg/kg) could improve myocardial performance in a myocardial infarction model.…”
Section: Pongkan Et Almentioning
confidence: 99%
See 2 more Smart Citations